PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI HAKIKAT BIOLOGI TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI 1 RAMBAH HILIR TAHUN PEMBELAJARAN 2014/2015 - Sani, Miftahul; Afifah, Nurul; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study aimed to determine the effect of cooperative learning jigsaw on the nature of the biological materialto the results of class X student of SMA Negeri 1 Rambah Rambah Hilir. This was a Quasi-Experiments Study. Samples were the Student in class X1 and X2. Data collecting techniques in this study was a test. The data analysis technique is a âtâ test. Result showed that the value of tcount = 5.128 and ttable at 5% significance level of 2.021. This suggests that tcount > ttable that the null hypothesis is rejected and the alternative hypothesis is accepted.